Rasch model-based grit exploration in university of indonesia students: a descriptive study using the grit-o scale - Andrianie, Santy; Bariyyah, Khairul; Ifdil, Ifdil; Soejanto, Laily Tiarani; Setyorini, Setyorini; Ariyanto, Restu Dwi; Mamahit, Henny Cristine (COUNS-EDU: The International Journal of Counseling and Education, 2024)
This study aims to describe the level of grit of students in Indonesia and its technicality with their academic success. Grit, which consists of persistence and passion towards long-term goals, is an important factor in academic success. Using a quantitative descriptive approach, this study involved 461 students from various universities in Indonesia. Data were collected using the Grit-O Scale which measures two dimensions of grit, namely consistency and consistency of interest. The results of the analysis using the Rasch Model showed that most students had a moderate level of grit, with some students showing high or low levels. These findings illustrate the challenges faced by students in maintaining academic motivation and persistence. This study is expected to provide useful insights for the development of educational programs that support the improvement of students' grit, with the aim of improving their academic achievement and readiness to face global challenges in the future.